2017
DOI: 10.1007/s10067-017-3671-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypomyopathic dermatomyositis associated with interstitial lung disease and good response to mycophenolate mofetil: case-based review

Abstract: Hypomyopathic dermatomyositis (HDM) is a rare form of dermatomyositis (DM). Interstitial lung disease (ILD) associated with clinically amyopathic DM (CADM-ILD) or hypomyopathic DM (HDM-ILD) is a rare condition with a more unfavorable prognosis than ILD associated with classic DM (CDM-ILD). There is no effective treatment for HDM-ILD. A 62-year-old woman with a 6-month history of chronic polyarthritis and myalgia presented skin lesions characteristic of DM (erythematous lesion on extensor surface of elbows, Got… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…MMF given to 50 children with JDM was both corticosteroid sparing and decreased muscle and skin inflammation without leukopenia or an increased number of infections (103). Adult DM with ILD responded well to MMF (104). Associated with congenital malformations, MMF should be discontinued 7 weeks before a planned pregnancy.…”
Section: Childhood and Adult Onset Dermatomyositis Have Differing Feamentioning
confidence: 99%
“…MMF given to 50 children with JDM was both corticosteroid sparing and decreased muscle and skin inflammation without leukopenia or an increased number of infections (103). Adult DM with ILD responded well to MMF (104). Associated with congenital malformations, MMF should be discontinued 7 weeks before a planned pregnancy.…”
Section: Childhood and Adult Onset Dermatomyositis Have Differing Feamentioning
confidence: 99%
“…While there was no significant difference in infection rates between the two groups, the incidence of leukopenia was higher in the new treatment group. 17 An improvement in %FVC and a reduction in steroid dosage have also been reported in 32 PM/DM-ILD cases using MMF. 18 One case of an anti-MDA5 antibody-positive DM-ILD patient treated with PSL, MMF, and IVIg has been reported, with improvement in cutaneous and muscular symptoms and without worsening of ILD.…”
Section: Discussionmentioning
confidence: 80%
“…Koyama et al. reported that clinical symptoms, respiratory function, and radiographic findings improved in eight of 10 patients with CADM‐ILD treated with MMF 17 . An improvement in %FVC and a reduction in steroid dosage have also been reported in 32 PM/DM‐ILD cases using MMF 18 .…”
Section: Discussionmentioning
confidence: 96%
“…In ARS‐DMIP patients with high relapse risk, slow reduction of GC and CNI dosage is recommended to suppress IP activity in the long‐term. When the reduction of CNI dosage is inevitable because of adverse events, additional combination treatment should be considered using intravenous cyclophosphamide therapy, azathioprine and mycophenolate mofetil which have been reported to be effective for DMIP …”
Section: Discussionmentioning
confidence: 99%